Reduced cytotoxicity of silver ions to mammalian cells at high concentration due to the formation of silver chloride - Zhang, S.; Du, C.; Wang, Z.; Han, X.; Zhang, Kun; Liu, Lihong (Pergamon, 2013)
Silver-containing antimicrobial agents are used in various medical products. However, their toxicity to mammalian cells has not been sufficiently evaluated. Numerous studies have unveiled evidence of significant antimicrobial properties associated with Ag ions. In cell culture media or human body fluids, the free Ag+ has rich opportunities to complex with Cl-. Surprisingly, studies on the toxicity of solid form AgCl(s) to mammalian cells are quite limited. In this study, we evaluated the cytotoxicity of Ag ions and silver chloride colloids on red blood cells and human mesenchymal stem cells (hMSCs). The adverse effects of silver chloride on red blood cells and hMSC were viewed by SEM and LIVE/DEAD viability staining, respectively. Among different tested chemical forms of silver, AgCl was identified to be the least cytotoxic. Moreover, a decline in the cytotoxicity of AgCl at significantly high concentrations was observed. We attributed the reduced cytotoxicity to aggregated AgCl which limited the bioavailability of free Ag+ ions.